Study of Pollution Levels of heavy metals residues in the locally produced cheese & emulsifying salts - Al-Shdidi, Ahmed M.S. (The Iraqi Journal of Veterinary Medicine, 2010)
The study was conducted to indicate the compartive measurements of heavy metals residues levels were detected by Atomic Absorption Spectrophotometer in 10 random samples of locally processed cheeses and in 20 random samples of emulsifying salts collectd from different areas in Baghdad , results showed that such cheese of low quality and did not meet both local and international Dairy products standards , Such findings of high concentration of heavy metals residues indicate that the emulsifying salts used in processing were not nutritional but of industrial origin and unfit for human consumption . The results show that is the concentration *[p.p.m.] of heavy metals residues **(±MD) in the locally processed cheeses samples were < 0.1±0.001 p.p.m. for both of Cd. & Mn. , 3.5±0.28 p.p.m. for Fe. , < 0.05±0.001 p.p.m. for Pb. , 7.3±0.3 p.p.m. for Zn. & 0.24±0.01p.p.m. for Cu. .. While the concentration *[p.p.m.] of heavy metals residues **(±MD) in the Emulsifying salts were 1.55±0.145 p.p.m. for Cd. , 1.7±0.16 p.p.m. for Mn. , 16±1.12 p.p.m. for Fe. , 3.15±0.275 p.p.m. for Pb. , 233.1±5.6 p.p.m. for Zn. & 1.95±0.085 p.p.m. for Cu.